“Half a man?” Still a human: Narratives on the impact of a spinal cord injury on coloured men living with paraplegia - Louw, Helenard Kingsley Madiba (Gender Studies, 2019)
There is an overwhelming body of research in the Global North that focuses on the narratives of the impact of a spinal cord injury on men living with paraplegia, while existing research in South Africa and the Global South lacks knowledge on these narratives. This study explored the narratives on the impact of a spinal cord injury on fifteen coloured men living with paraplegia on the Cape Flats. This study adopted a life story approach, as a primary research methodology, and examined how these men constructed and told their life stories, how meanings and experiences of living with paraplegia were conveyed, and how they negotiated the intersection of disability, masculinity, race, class and sexuality in their lives. A participatory action research (PAR) methodology, photo-voice, was used as a complimentary methodology which depicted how these men visually represented the way they think main-stream society sees them and the way they see themselves. Drawing on Frank’s (1995) work on narratives and illness, this study used two life stories and theoretically shows how life stories with a central focus on paraplegia as a spinal cord injury are constructed and narrated. Through a narrative thematic analysis, themes and sub-themes highlighted the complexities and tensions in the construction and performance of masculinities after the injury. The following themes emerged from the narratives: feelings of shame and infantilization, a loss of independency, dehumanizing social perceptions of being a man living with a disability, vulnerability to violence, and challenges in sexual intercourse and intimacy. The narratives also show that a man in this context can develop a positive sense of self through learning to live independently, strategies to prevent violence, redefining sex, and redefining what it means to be a man and ‘disabled’.